Ex situ conservation of the African elephant (Loxodonta africana): characterisation of the largest elephant reserve in Latin America (Revista Sistemas de Producción Agroecológicos, 2023)
The drastic decline in wild populations of the African elephant (Loxodonta africana) over the last 50 years has forced us to complement in situ conservation programmes with human-maintained populations that act as a gene bank and raise awareness of the loss of the species. In partnership with the International Elephant Foundation (IEF), Africam Safari participates in the conservation of African elephants by supporting and funding projects aimed at preserving the species and maintaining the largest herd of elephants in Latin America at its facilities. The following report aims to characterise the main processes carried out at Africam Safari that have led to the effective reproduction of specimens and the subsequent birth of more than 10 African elephant calves in the last 6 years.
Keywords: African elephant; Conservation programme; Ex situ